Retention depends on the balance of creative idea with Practical Implementation of Rectangle Communications Ltd. - Arefin, M. M. Bahalul (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.